Decadal trends in soil and grain microelement concentrations indicate mainly favourable development in Finland. Issue 5 (15th August 2022) - Soinne, Helena; Kurkilahti, Mika; Heikkinen, Jaakko; Eurola, Merja; Uusitalo, Risto; Nuutinen, Visa; Keskinen, Riikka
Abstract: Background: Observations on declining nutrient contents in crops have raised concerns about soil fertility and food quality. Long‐term monitoring data are valuable in exposing trends and indicating the need for interventions. Aims: This study aimed to assess the soil microelement status and grain nutritional value on a national scale in Finland over the last decades. Methods: Using nationwide sets of samples and time‐series datasets, temporal trends in readily available zinc, copper, boron, iron, manganese, cadmium, molybdenum, nickel, aluminium, cobalt, and lead in cultivated soils of Finland during 1974–2018 and the corresponding total element concentrations in grains of oats and barley during 1988–2019 were determined. Results: In soil, initially increasing trends of element concentrations tended to prevalently level off towards the end of the study period. A decreasing trend was observed only for cadmium and zinc in coarse soils. In grains of barley and oat, aluminium and lead concentrations decreased between 1988 and 2019. Barley grains exhibited a decreasing trend in manganese and cobalt, whereas an increasing trend was detected for copper and iron in oats. Conclusions: No alarming decreases in micronutrient contents in agricultural soils or cereal grains were detected over the study period. In grains, the concentrations of potentially toxic elements decreased. Although the nationwide micronutrient status in Finland is on average satisfactory or good, local micronutrient deficiencies may occur.